Bureaucrat and Politician Ali Şakir Ağanoğlu’s Opinion On Banking - Koraltürk, Murat; Varlı Binagül, Arzu (Journal of Applied And Theoretical Social Sciences, 2021)
Starting his career at Ziraat Bank as assistant inspector, Ali Şakir Ağanoğlu (1915-2005) later served as the bank's general manager and held membership in the board of directors. He also later played an important role in politics as a deputy, senator and minister and was among the leading figures in the institutionalization of business education in Turkey. Ağanoğlu expressed his views on economics in his books and particularly his articles, which also deal with banking as his area of greatest experience. Presenting an overview of Ağanoğlu's education as well as professional and political career, this article discusses his views on the development status of banks particularly during the period of planned economic growth.